2017
DOI: 10.1111/acel.12697
|View full text |Cite
|
Sign up to set email alerts
|

PGC‐1α affects aging‐related changes in muscle and motor function by modulating specific exercise‐mediated changes in old mice

Abstract: SummaryThe age‐related impairment in muscle function results in a drastic decline in motor coordination and mobility in elderly individuals. Regular physical activity is the only efficient intervention to prevent and treat this age‐associated degeneration. However, the mechanisms that underlie the therapeutic effect of exercise in this context remain unclear. We assessed whether endurance exercise training in old age is sufficient to affect muscle and motor function. Moreover, as muscle peroxisome proliferator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 45 publications
4
58
1
Order By: Relevance
“…In parallel to improving calcium homeostasis and downregulation of proteins that accumulate in tubular aggregates such as CSQ1, a central role for PGC-1α in this context is further substantiated by our SDH staining and electron microscopy data as well as other studies that revealed a strong preference for tubular aggregate formation in glycolytic fibers (59,60). The potent effect of PGC-1α in driving an oxidative muscle fiber shift (32,33,61) thus likely further contributes to the inhibition of tubular aggregate formation. In light of our data, it would be interesting to study whether increased muscle PGC-1α levels prevent tubular aggregate formation in mice with tubular aggregateassociated myopathies (51,62).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In parallel to improving calcium homeostasis and downregulation of proteins that accumulate in tubular aggregates such as CSQ1, a central role for PGC-1α in this context is further substantiated by our SDH staining and electron microscopy data as well as other studies that revealed a strong preference for tubular aggregate formation in glycolytic fibers (59,60). The potent effect of PGC-1α in driving an oxidative muscle fiber shift (32,33,61) thus likely further contributes to the inhibition of tubular aggregate formation. In light of our data, it would be interesting to study whether increased muscle PGC-1α levels prevent tubular aggregate formation in mice with tubular aggregateassociated myopathies (51,62).…”
Section: Discussionsupporting
confidence: 79%
“…7). In the light of our present and other recent findings (61,70,72), PGC-1α modulation, e.g. by exercise or pharmacological interventions, represents an attractive approach to reduce weakness, frailty and other pathological alterations associated with skeletal muscle aging, along with additional potential benefits on the heart (71).…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, muscle‐specific PGC‐1α deletion led to a premature decrease in running capacity in 12‐month‐old mKO animals (Figure c). These data correlate with the balance, muscle strength, and fiber size changes upon PGC‐1α modulation in old animals (Gill, Santos, Schnyder, & Handschin, ). Together, these results clearly show that PGC‐1α is not only an essential regulator of mitochondrial function and dynamics in young and old animals, but also prevents the age‐associated decline of these systems.…”
Section: Resultssupporting
confidence: 67%
“…In parallel to improving calcium homeostasis and downregulation of proteins that accumulate in tubular aggregates such as CSQ1, a central role for PGC‐1α in this context is further substantiated by our SDH staining and electron microscopy data as well as other studies that revealed a strong preference for tubular aggregate formation in glycolytic fibers (Funk et al, ). The potent effect of PGC‐1α in driving an oxidative muscle fiber shift (Gill et al, ; Handschin, Chin, et al, ; Lin et al, ) thus likely further contributes to the inhibition of tubular aggregate formation. In light of our data, it would be interesting to study whether increased muscle PGC‐1α levels prevent tubular aggregate formation in mice with tubular aggregate‐associated myopathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation